The roles of the Malay in the process of Islamization of the Malay World: a preliminary study - Abdul Jalil, Mohd. Noh (Postgraduate Program Sunan Gunung Djati State Islamic University (UIN), 2015)
This paper will deal with problems concerning issues and theories of Islamization of the Malay world, with particular reference to the absence of the important element in these theories, which is the role and contribution of the Malays towards the process of Islamization in this region. Furthermore, there will be a discussion of the problem of generalization of existing theories, as well as issues concerning the limited amount of local evidence to support these theories. Sources for this analysis will be taken from studies of inscriptions, as well as early Malay texts, religious and non-religious texts. Comparison between the existing theories and direct and indirect evidence from sources will be used to elaborate on this matter. The ability of the early Malays to adopt and adapt foreign practices suggests that they also contributed to the entire process of Islamization of the Malay world one way or the other.